2011
DOI: 10.1007/s10517-011-1222-2
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Apoptosis and Expression of Heat Shock Proteins in Peripheral Blood Lymphocytes of Patients with Myocardial Infarction

Abstract: We studied activity and dynamics of apoptosis of peripheral blood lymphocytes in patients with myocardial infarction and analyzed the relationship of these processes with expression of heat shock proteins with a molecular weight of 70 kDa playing an essential role in preventing cell death. Thus, we first demonstrated activation of apoptosis in peripheral blood cells of patients with myocardial infarction compared to the control (healthy individuals) and revealed the expected negative correlation between the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
(16 reference statements)
0
4
0
1
Order By: Relevance
“…The caspase-3, the reliable marker of apoptosis and the final common product of the extrinsic and intrinsic apoptotic pathways, was significantly increased in the ISP group [ 77 ]. The persistent apoptosis after MI leads to myocardial fibrosis, cardiac remodeling, and pathological alteration in cardiac function [ 78 , 79 ]. The results of our study revealed that pre-and co-treatment with TQ in the third group significantly attenuated apoptosis by decreasing the myocardial tissue level of caspase-3, which indicates the anti-apoptotic properties of TQ.…”
Section: Discussionmentioning
confidence: 99%
“…The caspase-3, the reliable marker of apoptosis and the final common product of the extrinsic and intrinsic apoptotic pathways, was significantly increased in the ISP group [ 77 ]. The persistent apoptosis after MI leads to myocardial fibrosis, cardiac remodeling, and pathological alteration in cardiac function [ 78 , 79 ]. The results of our study revealed that pre-and co-treatment with TQ in the third group significantly attenuated apoptosis by decreasing the myocardial tissue level of caspase-3, which indicates the anti-apoptotic properties of TQ.…”
Section: Discussionmentioning
confidence: 99%
“…Persistent MI is accompanied with apoptosis and progressive loss of cells with subsequent cardiac remodeling, ventricular dilation, myocardial fibrosis, gradual decrease of cardiac function and heart failure after progression of myocardial infarction ( Konstantinova et al., 2011 ; Rondeau et al., 2011 ). Bcl-2 expression blocks features of apoptosis, like plasma membrane blebbing, DNA cleavage, and nuclear condensation.…”
Section: Discussionmentioning
confidence: 99%
“…Persistent apoptosis leads to the progressive loss of cells, which is known to be an important cause for myocardial fibrosis, ventricular dilation, cardiac remodeling, gradual decrease of cardiac function and heart failure following myocardial infarction (10,11). Therefore, inhibition of apoptosis following myocardial infarction and protecting myocardial cells against loss has become an important focus (12).…”
Section: Discussionmentioning
confidence: 99%